Elkem Iceland: Furnace unbalance and preventive measures - Petre Manolescu 1984- (2011)
The production of ferrosilicon is done in submerged electric arc furnaces. The current in the furnace can be adjusted by raising/lowering the electrodes which in turn adjust the impedance. Ideally the current in each electrode should be equal. When the electrodes are in the top or bottom position there is no room for adjusting the impedance and the furnace goes off balance. The purpose of this project is to discuss the feasibility of adjusting the voltage provided by three single-phase tap transformers in order to compensate for the furnace unbalance. The transformers are connected in ∆ and operate on the same tap number. In order to adjust the voltage for one electrode the tap number must be lowered/raised on two transformers. Due to the ∆ connection circular currents arise in the circuit when unsymmetrical taps are selected, overloading the transformers. An estimate of the impedance within the transformers and the elctrical circuit leading to the electrodes is done in order to find the size of the circular currents and their effects.